2014
DOI: 10.1016/j.antiviral.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Use of FDA approved therapeutics with hNTCP metabolic inhibitory properties to impair the HDV lifecycle

Abstract: Worldwide there are approximately 240million individuals chronically infected with the hepatitis B virus (HBV), including 15-20million coinfected with the hepatitis delta virus (HDV). Treatments available today are not fully efficient and often associated to important side effects and development of drug resistance. Targeting the HBV/HDV entry step using preS1-specific lipopeptides appears as a promising strategy to block viral entry for both HBV and HDV (Gripon et al., 2005; Petersen et al., 2008). Recently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…These seminal findings established NTCP as an HBV and HDV receptor, a demonstration that has been independently confirmed and extended (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Consequently, NTCP substrates or inhibitors such as tauroursodeoxycholic acid (TUDCA), cyclosporine, irbesartan, and ritonavir could suppress ccHBV or HDV infection (18,(20)(21)(22)(23)(24). Nevertheless, NTCP-reconstituted HepG2 cells cultured in the presence of DMSO reportedly released up to 100 times more HBeAg than differentiated HepaRG cells after ccHBV infection, but comparable amounts of HBsAg (18).…”
mentioning
confidence: 99%
“…These seminal findings established NTCP as an HBV and HDV receptor, a demonstration that has been independently confirmed and extended (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Consequently, NTCP substrates or inhibitors such as tauroursodeoxycholic acid (TUDCA), cyclosporine, irbesartan, and ritonavir could suppress ccHBV or HDV infection (18,(20)(21)(22)(23)(24). Nevertheless, NTCP-reconstituted HepG2 cells cultured in the presence of DMSO reportedly released up to 100 times more HBeAg than differentiated HepaRG cells after ccHBV infection, but comparable amounts of HBsAg (18).…”
mentioning
confidence: 99%
“…As the immunosuppressive activity of cyclosporine was dispensable for anti-HBV activity, we showed that nonimmunosuppressive derivatives, including alisporivir, which is under clinical development for treatment of chronic hepatitis C, significantly inhibited HBV infection, suggesting that these compounds are potential anti-HBV candidates (17). In addition, three FDA-approved agents, irbesartan, ezetimibe, and ritonavir, which are already known to inhibit NTCP transporter activity, reduced LHBs-dependent viral infection (32)(33)(34)36). Although already known NTCP inhibitors have been reported to inhibit viral infection, there is no report identifying novel compounds that target NTCP and inhibit HBV infection.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, vanitaracin A was also effective against HDV infection, as in the case of anti-HBV entry inhibitors reported so far (32,35,51). Coinfection of HDV with HBV occurs in ϳ15 million people worldwide, and HDV infection causes more severe viral hepatitis than does hepatitis B (52)(53)(54).…”
Section: Discussionmentioning
confidence: 94%
“…However, further experiments and clinical survey are needed to determine whether irbesartan will be effective against HBV infection and spread in vivo. Considering that HBV and its satellite virus hepatitis D virus (HDV) both utilize NTCP for their entry, we hypothesize that irbesartan could also exert anti-HDV effects which was reported very recently (Blanchet et al, 2014) and this might be helpful for HBV/HDV coinfection therapy.…”
Section: Discussionmentioning
confidence: 93%